En Litterær Biografi og Narrative Identitetsbilleder Dorrit Willumsens Roman Marie. Madame Tussauds LIV - Krysztofiak, Maria (Folia Scandinavica Posnaniensia, 2012)
The article focuses on the narrative construction of identity in the biographical novel about the life of Madame Tussaud written by the Danish author Dorrit Willumsen. A specific biographical narration technique of Willumsen is the starting point for discussing two interweaving layers of biographical discourse: the historical literary biography and the internal biography (lifeline as a story). Willumsen`s open dialogue of images and words shapes the narration to cross the frame of the principal character`s historical time and places Willumsen`s novel in the European context of narrative literature on artistic images of identity.